The Effect of Ti-doped on the Structure of Y134 and Y257 Superconductors - Kruaehong*, Thitipong; Sujinnapram, Supphadate; Udomsamuthirun, Pongkaew; Nilkamjon, Tunyanop; Ratreng, Sermsuk (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The powder of Y134, Y257 and Ti composite was synthesized by solid state reaction. The crystal structure of the powder was investigated by using powder X-ray diffraction. The raw data of XRD was characterized for phase separation of composition. The samples consist of a superconducting phase with orthorhombic structure and Pmmm space group and a non-superconducting phase that have various structures and space groups. The Ti doped affected the increasing c lattice parameters and superconducting phase. The impurity phase had no effect on increasing the c lattice superconducting phase. The c lattice parameters and superconducting phase was increased following the Ti-doped. Keywords: Y134 superconductor, Y257 superconductor, titanium-doped Corresponding author: Tel.: +66 851 09 0567 Fax: +66 77355 666 E-mail: kruaehong@hotmail.com